MITOS LORELEI DALAM NOVEL MÃ„RCHEN II : RHEIN MÃ„RCHEN ANALISISSTRUKTURALISME LEVI-STRAUSS - FARID BURHANUDDIN, ISNAN (UNIVERSITAS NEGERI SURABAYA, 2016)
This thesis examines the myth of Lorelei in the future based on the myth of female Romantik believed by Germansociety at that time. The focus of this research is a character in the novel Frau Lureley Märchen II: Rhein MärchenClemens Brentano work. This study aims to determine the structure of the myth of the myth in the character FrauLureley using the approach of structuralism Levi-Strauss. The method used in this research is descriptive qualitativemethod. Assessment of this type aims to reveal various qualitative information to describe accurately the properties ofmatter (individual / group) with analysis and interpretation of data. Keywords : Lorelei, Lorelei myth, the structure of myth, function of myth